Effect of Build Plate Material and Temperature on Adhesion Performance in Fused Filament Fabrication of HIPS and PP - Bondan Wiratmoko Budi Santoso; Andreas Sugijopranoto; Budi Arifvianto; Muslim Mahardika; Th. Adi Nugroho; Paulus Wisnu Anggoro (Jurnal Rekayasa Mesin, 2025)
Adhesion between the printed part and the buildplate was a critical factor governing process stability, dimensional accuracy, and failure prevention in fused filament fabrication (FFF) technology. This study aimed to investigate the effects of build plate material and build plate temperature on interlayer adhesion performance and build-plate adhesion of high-impact polystyrene (HIPS) and polypropylene (PP). The research method used was an experimental approach involving the fabrication of standardized specimens using an FFF-based 3D printer, evaluation of interlayer bonding through tensile testing in accordance with ISO 527-3, and measurement of build-plate adhesion using a specially designed detachment test apparatus integrated with a universal testing machine, complemented by fracture morphology analysis using scanning electron microscopy. The results showed that increasing build plate temperature significantly improved interlayer adhesion strength and fracture surface width in HIPS, particularly at temperatures approaching its glass transition temperature, indicating enhanced molecular diffusion and improved interfacial bonding quality, whereas PP exhibited poor adhesion performance on all tested build plate surfaces due to early warping and interfacial void formation. Optimal and stable build-plate adhesion was achieved only for the HIPS–PEI combination at a build plate temperature of 105 °C, while ultrabed and glass build plates did not demonstrate adequate adhesion performance. These findings confirmed the importance of compatibility between thermal conditions and build plate surface characteristics in FFF processes and highlighted the necessity of material modification or additional surface treatment to improve the printability of PP.